Grade 2 Students Perception Of Mathematics Learning - Inayatus Saadah Dalimunthe; Safril Abidin Hasibuan; Poltak Pembangunan Harahap; Almira Amir (International Journal of Community Service (IJCS), 2026)
This study aims to describe the perception of grade 2 elementary school students towards mathematics learning from the cognitive, affective, and conative dimensions. The research uses a qualitative approach with a descriptive design. The subject of the study was a grade 2 student at a public elementary school in West Lombok Regency. Data collection techniques were carried out through participatory observation, semi-structured interviews, and student perception questionnaires. The data was analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that most students have a positive perception of mathematics learning if the material is delivered in a concrete, contextual, and fun manner. On the cognitive dimension, students understand mathematics as a useful subject in everyday life, although some of the material is still considered difficult. In the affective dimension, students show a sense of joy when learning using games and interesting media, but some students still experience anxiety when facing problems that are considered complicated. In the conative dimension, students with positive perceptions tend to be more active in learning mathematics. Factors that affect student perception include teachers' teaching methods, the use of learning media, and family support. The findings of the study confirm the importance of learning mathematics that is concrete, interactive, and in accordance with the developmental characteristics of elementary school students in the lower grades.